Perancangan User Experience Aplikasi Mobile Online Therapy untuk Mengatasi Depresi bagi Remaja menggunakan Metode Human-Centered Design - Lalu Muhamad Arfian Arya Gandhi; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Every individual have problems that must be faced, both physically or mentally. Data from the World Health Organization in 2014, showed that depression was the cause of global disease and illness for youth, with suicide as the third largest leading cause of death behind road traffic injuries, and HIV/AIDS. Data from Basic Health Research (Riskesdas) in 2018, it was found that the prevalence of mental health disorders with age 15 years old and over reached around 6.1% of the total population of Indonesia or the equivalent of 11 million people. From a study conducted with adolescents with an age range of 15-24 years old had a percentage of 6.2%, and major depression will experience a tendency from self-harm to suicide. From these problems, there is a solution offered, is to conduct online therapy. Online Therapy aims to help people with depression to be able to cure their depression with proper treatment through online therapy services. This method is devoted for mental health healing, where a therapist provides psychological advice and support via the internet. In this design, the researcher uses the Human-Centered Design method approach in order to create application designs according to user needs. The final result of this research is a high-fidelity prototype with a good usability score. The three aspects of the usability value was obtained were the effectiveness aspect from the user side gets a score of 88%, and from the psychologist side gets a score of 84%. The efficiency aspect using time based efficiency from the user side gets a score of 0.103 goal/sec, and from the psychologist side gets a score of 0.077 goals/sec. And the satisfaction aspect by using the SUS questionnaire from both sides of user and psychologist gets a score of 80.5 with grade A-, adjective good, and acceptable.